Maternal and Cord Blood Adiponectin Multimeric Forms in Gestational Diabetes Mellitus: A prospective analysis - Ballesteros, Mónica (American Diabetes Association, 2011)
OBJECTIVE: To analyze the relationship between maternal adiponectin (mAdiponectin) and cord blood adiponectin (cbAdiponectin) multimeric forms (high molecular weight [HMW], medium molecular weight [MMW], and low molecular weight [LMW]) in a cohort of gestational diabetes mellitus (GDM) and normal glucose–tolerant (NGT) pregnant women. RESEARCH DESIGN AND METHODS: A total of 212 women with a singleton pregnancy, 132 with NGT and 80 with GDM, and their offspring were studied. Maternal blood was obtained in the early third trimester and cord blood was obtained at delivery. Total adiponectin and the multimeric forms of adiponectin were determined in cord blood and maternal serum. Spearman rank correlation and stepwise linear correlation analysis were used to assess the relationship between cbAdiponectin levels and clinical and analytical parameters. RESULTS: No differences in cbAdiponectin concentration or its multimeric forms were observed in the offspring of diabetic mothers compared with NGT mothers. The HMW-to-total adiponectin ratio was higher in cord blood than in maternal serum, whereas the MMW- and LMW-to-total adiponectin ratio was lower. Cord blood total and HMW adiponectin levels were positively correlated with birth weight and the ponderal index (PI), whereas cord blood MMW adiponectin was negatively correlated with the PI. In addition, cbAdiponectin and its multimeric forms were correlated with mAdiponectin concentrations. In the multivariate analysis, maternal multimeric forms of adiponectin emerged as independent predictors of cbAdiponectin, its multimers, and their distribution. CONCLUSIONS: cbAdiponectin concentrations are independently related to mAdiponectin levels and unrelated to the diagnosis of GDM. Maternal multimeric forms of adiponectin are independent predictors of the concentrations of cbAdiponectin and its multimeric forms at delivery.